Patient-reported symptom burden of chronic graft versus host disease: a systematic literature review. Issue 10 (2nd October 2020) - Csanádi, Marcell; Ágh, Tamas; Farkas-Ráduly, Szabolcs; Gros, Blanca; Tapprich, Christoph; Trudeau, Jeremiah J; Lipton, Jeffrey H; Mattsson, Jonas
ABSTRACT: Introduction: Chronic graft-versus-host disease (GVHD) is a life-threating complication of allogeneic hematopoietic stem cell transplantation (HSCT) leading to high morbidity and quality of life issues. We conducted a systematic literature review on the patient reported symptom burden of chronic GVHD. Areas covered: English-language articles published between 2005 and November 2018 were searched using CENTRAL, EMBASE and MEDLINE. Studies that used the 2005 or 2015 National Institute of Health consensus criteria for the diagnosis and staging of chronic GVHD were included. Expert opinion: Patient reported symptom burden was widely assessed in the literature (n = 38). The Lee Chronic GVHD Symptom Scale was the most frequently used instrument (n = 28), followed by the NIH Patient-reported Symptom scores (n = 11). Association of symptom burden with clinical outcome assessment endpoints (e.g. mortality) and with quality of life measures was investigated by fairly low number of studies with limited generalizability. By systematically investigating the influencing factors of symptom burden this review helps to better understand patients' perceptions and may help improving the management and care of chronic GVHD. However, data on influencing factors was quite diverse, which indicates that specific questions identified as research gaps need to be incorporated in randomized clinical trials in a more systematic way.